The Zygotic Division Regulator ZAR1 Plays a Negative Role in Defense Against Botrytis cinerea in Arabidopsis - Chen, Lijuan; Xiao, Jiahui; Song, Yuxiao; Li, You; Liu, Jun; Cai, Huiren; Wang, Hong-Bin; Liu, Bing (Frontiers in Plant Science, 2021)
A phosphorylation/dephosphorylation cycle at tyrosine 428 (Y428) of CHITIN ELICITOR RECEPTOR KINASE 1 (CERK1) plays an essential role in chitin triggered immunity in Arabidopsis thaliana. Here, we used a differential peptide pull-down (PPD) assay to identify factors that could participate downstream of this cycle. We identified ZYGOTIC ARREST 1 (ZAR1) and showed that it interacts with CERK1 specifically when the Y428 residue of CERK1 is dephosphorylated. ZAR1 was originally characterized as an integrator for calmodulin and G-protein signals to regulate zygotic division in Arabidopsis. Our current results establish that ZAR1 also negatively contributes to defense against the fungus Botrytis cinerea and plays a redundant role with its homolog ZAR2 in this process. The zar1-3 zar2-1 double mutant exhibited stronger resistance to B. cinerea compared to zar1-3 single mutant, zar2-1 single mutant, and wild-type plants. Moreover, the inducible expression of numerous defense response genes upon B. cinerea infection was increased in the zar1-3 zar2 double mutant, consistent with a repressive role for ZAR proteins in the defense response. Our findings thus provide insight into the function of ZAR1 in multiple defense and developmental regulation pathways.